Effect of inclusion of condensed tannin with differing molecular weight in diet rich in sunflower oil on ruminal pH and kinetics of gas production in vitro - Petlum, Anan; Paengkoum, Pramote; Liang, Juan Boo; Vasupen, Kraisit; Paengkoum, Siwaporn (Faculty of Animal Husbandry, Brawijaya University, 2017)
Condensed tannins (CTs) play a very important role in ruminant feeding. However, their chemical structure and molecular weight have effect on their biology property and efficacy to rumen manipulation. This study was aimed to investigate the effect of CTs with differing molecular weigh on in vitro gas production. Inclusion of high molecular weight CTs (HMWCT) at 2 and 4 mg/100 mg DM substrate had significantly decreased in vitro gas production rate constant (c) (P < 0.05) and total gas production (P < 0.001).